Side Effects of Human Drug Use: An Overview of the Consequences of Eels’ Exposure to Cocaine - Luigi Rosati; Ivana Caputo; Lillà Lionetti; Mayana Karoline Fontes; Camilo Dias Seabra Pereira; Anna Capaldo (Fishes, 2023)
The widespread use of drugs is a global problem which affects not only humans but also the environment around them, as research is showing the presence of these substances in different environmental matrices, like air, water, and soil. Above all, due to the remarkable pharmacological properties of drugs, it is discovered that organisms accidentally exposed to them, as aquatic organisms, undergo behavioral and physiological changes that can compromise their health, survival, and reproduction ability. In addition to this, we must consider the ability of some drugs to accumulate within these organisms, thus entering the food chain, and the possible interactions that drugs in water can establish with each other and with other possible pollutants, making the final effects on exposed organisms unpredictable. This article is an overview of the effects of one of these drugs, cocaine, one of the drugs commonly found in the aquatic environment, on European eel, an endangered species and known biomonitor of aquatic contamination.